Analysis Of Macrobenthic Community Structure In Relation To Different Environmental Conditions In Three Harbours In The North Tyrrhenian Sea (Italy). Preliminary Study - BEDINI, R.; CANALI, M.G.; CAPPAGLI, M. (Mediterranean Marine Science, 2003)
Studies on benthic communities are being widely used in monitoring pollution effects, using both the methodologies provided from the national laws in various countries and experimental innovative methodologies of research. We have carried out a preliminary study on macrobenthic communities (zoobenthos and phytobenthos) in three harbours, one of which (Piombino) receives wastewater from industry and is also subject to heavy shipping traffic. The other two (Porto Santo Stefano and Portoferraio) enjoy great tourist traffic but no industrial waste, and they have been selected in order to find possible differences between populations of animals present in unpolluted and polluted areas. The results show that there are no outstanding differences in the sessile and sedentary bentological population parameters of the studied harbours. We probably do not have an adequate historical data set of the species living in the study areas to detect the effects of pollution, and the sessile living animal species we found may have adapted to the current situation, since living species typical of very clean waters were found.